Anaerobic Degradation of Sulfated Polysaccharides by Two Novel Kiritimatiellales Strains Isolated From Black Sea Sediment - van Vliet, Daan M.; Palakawong Na Ayudthaya, Susakul; Diop, Sally; Villanueva, Laura; Stams, Alfons J. M.; Sánchez-Andrea, Irene (Frontiers in Microbiology, 2019)
The marine environment contains a large diversity of sulfated polysaccharides and other glycopolymers. Saccharolytic microorganisms degrade these compounds through hydrolysis, including the hydrolysis of sulfate groups from sugars by sulfatases. Various marine bacteria of the Planctomycetes-Verrucomicrobia-Chlamydia (PVC) superphylum have exceptionally high numbers of sulfatase genes associated with the degradation of sulfated polysaccharides. However, thus far no sulfatase-rich marine anaerobes are known. In this study, we aimed to isolate marine anaerobes using sulfated polysaccharide as substrate. Anoxic enrichment cultures were set up with a mineral brackish marine medium, which was inoculated with anoxic Black Sea sediment from 2100 m depth and incubated at 15°C (in situ T = 8°C) for several weeks. Community analysis by 16S rRNA gene amplicon sequencing revealed the enrichment of Kiritimatiellaeota clade R76-B128 bacteria with the sulfated polysaccharides fucoidan and iota-carrageenan as substrate. We isolated two strains, F1 and F21, which represent two novel genera and a novel family within the order of the Kiritimatiellales. They were capable of growth on various mono-, di- and polysaccharides, including fucoidan. The desulfation of iota-carrageenan by strain F21 was confirmed quantitatively by an increase in free sulfate concentration. Strains F1 and F21 represent the first marine sulfatase-rich anaerobes, encoding more sulfatases (521 and 480, 8.0% and 8.4% of all coding sequences, respectively) than any other microorganism currently known. Specific encoded sulfatase subfamilies could be involved in desulfating fucoidan (S1_15, S1_17 and S1_25) and iota-carrageenan (S1_19). Strains F1 and F21 had a sulfatase gene classification profile more similar to aerobic than anaerobic sulfatase-rich PVC bacteria, including Kiritimatiella glycovorans, the only other cultured representative within the Kiritimatiellaeota. Both strains encoded a single anaerobic sulfatase-maturating enzyme which could be responsible for post-translational modification of formylglycine-dependent sulfatases. Strains F1 and F21 are potential anaerobic platforms for future studies on sulfatases and their maturation enzymes.